Conceptual design of a fixtureless reconfigurable automated assembly system - Dymond, F. S. D. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.